Implementation of outcome-based education in Universiti Putra Malaysia : a focus on students' learning outcomes. - Mohayidin, Mohd Ghazali; Suandi, Turiman; Mustapha, Ghazali; Konting, Mohd. Majid; Kamaruddin, Norfaryanti; Man, Nor Azirawani; Adam, Azura; Abdullah, Siti Norziah (Canadian Center of Science and Education, 2008)
The move towards applying outcome-based education in teaching and learning at tertiary education level has become an important topic in Malaysia. Apart from th e three learning domains; namely, cognitive, psychomotor and affective, the Ministry of Higher Education has determ ined eight learning outcomes which are important in providing wholesome quality education to students. Universiti Putra Malaysia has conducted a study to determine the extent to which these learning outcomes have been achieved. The result shows the overall perceived achievements were as follows: cognitive domain was at level four, psychomotor domain at level four and affective domain at level three. The Ministry’s set of learning outcomes revealed the following results: The highest score went to providing KNOWLEDGE to students, while the least achievable learning outcome was MANAGERIAL AND ENTREPRENEURIAL SKILLS. The results infer that soft-skills among students were lacking and this problem needs to be addressed quickly and effectively.